Modeling and characteristic of surge propagation in electrical power system using ATP-EMTP - 226494 Mak, Kah Wee (Skudai : Universiti Teknologi Malaysia, 2005)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2005